Visual metaphors in tourism advertisement as a potential persuasive method - Hishamuddin, Siri; Mohamad Faizuan, Mat; Mohamad Zamhari, Abol Hasan; Hakimi, Halim; Abdul Walid, Ali (IJIDECS, 2018)
In advertising field, the uses of visual metaphors are commonly applied to express meaning more creatively while in the same time without losing the entire connection of the genuine message passed on. This study had been conducted to evaluate the effects of visual metaphors in tourism advertisement. The study also highlights the persuasive effect of visual metaphors in advertising. By using several methods such as interpretive of post-modernist literature and interpretive of positivist literature, it had found that the metaphorical images play the important role in visual tourism advertisement in order to persuade the tourism consumers. It is confirm that visual metaphor could be used as one of advertisement strategy for tourism advertisement. This kind of approach was overwhelmingly changed the ordinary tourism visual advertisement. However the usage of visual metaphorical alone can still is debated, as an advertising style and fashion are always dynamic according to the required period.